2022
DOI: 10.1177/13548565221089218
|View full text |Cite
|
Sign up to set email alerts
|

Establishing networked misogyny as a counter movement: The analysis of the online anti-Istanbul convention presence

Abstract: We now live in an age of unhidden gender wars where direct violence occurs within online and offline spaces. These online spaces on Facebook, Twitter or Instagram become venues for attacks on gender and woman’s rights, as well as its intersection with race and ethnicity. Such online hate expressions and networked harassments channelled towards women provide clues for us, social scientists, to understand the underlying dynamics/nature of misogyny. In this paper, by studying the online misogynistic narratives de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…We chose not to advertise our study publicly and did not create an open call for study participation because we anticipated the risk of finding ourselves as targets of trolling and backlash attacks. Our concern was based on the increasing ‘anti-feminist resistance’ in Turkey in the recent years, especially issues around the Istanbul Convention and women’s rights (Eslen-Ziya, 2022). Although this limited our chances to reach out to more women and, thus, restricted the generalisability of our findings, due to the rich and diverse content of the interviews, we still consider our data adequate to make meaningful contributions in relation to our research goals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose not to advertise our study publicly and did not create an open call for study participation because we anticipated the risk of finding ourselves as targets of trolling and backlash attacks. Our concern was based on the increasing ‘anti-feminist resistance’ in Turkey in the recent years, especially issues around the Istanbul Convention and women’s rights (Eslen-Ziya, 2022). Although this limited our chances to reach out to more women and, thus, restricted the generalisability of our findings, due to the rich and diverse content of the interviews, we still consider our data adequate to make meaningful contributions in relation to our research goals.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, social media becomes a tool of conservative groups in showing their support for discriminatory policies and practices, spreading their messages, and suppressing the voices of marginalised individuals and groups. A very recent study, for instance, examining the widespread online counter-activism in Turkey, demonstrates how social media becomes an important tool for anti-feminist groups in channelling their hate and hostility towards feminists and LGBTIQ+ communities, and how their discourses are used by the state for anti-democratic aims (Eslen-Ziya, 2022).…”
Section: Online Advocacy Against Male Violence In Turkeymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, media misrepresentation and the government’s anti-LGBTQ rhetoric intensify these challenges. For example, Eslen-Ziya (2022) demonstrated how anti-gender groups used social media platforms to threaten women and LGBTQ individuals online in Turkey. She argued that while social media platforms provide a space for these groups, they also offer a space for anti-feminist groups to portray the LGBTQ movement as a threat to Turkish cultural norms and the Turkish family (Eslen-Ziya, 2022).…”
Section: Context: Turkish Lgbtq Community and Their Strugglesmentioning
confidence: 99%
“…For example, Eslen-Ziya (2022) demonstrated how anti-gender groups used social media platforms to threaten women and LGBTQ individuals online in Turkey. She argued that while social media platforms provide a space for these groups, they also offer a space for anti-feminist groups to portray the LGBTQ movement as a threat to Turkish cultural norms and the Turkish family (Eslen-Ziya, 2022). Similarly, a recent study found that social media activists in Turkey experience transmit-trap dynamics, where they are both empowered by and targeted within social media platforms (Parks et al, 2017).…”
Section: Context: Turkish Lgbtq Community and Their Strugglesmentioning
confidence: 99%